Repeat thyroid function tests for healthy older people are not needed. (1st March 2019) - Cook, Rob; Fortescue-Webb, Duncan; Taft, Rachel
The study: Roberts L, McCahon D, Johnson O, Haque MS, Parle J, Hobbs FR. Stability of thyroid function in older adults: the Birmingham Elderly Thyroid Study. Published on 28 August 2018 Br J Gen Pract 2018;68:e718-26. This study was funded by the National Institute for Health Research School for Primary Care Research (SPCR). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000703/repeat-thyroid-function-tests-for-healthy-older-people-are-not-needed